Increasing Innovative Performance through Organization Culture, Work Satisfaction and Organization Commitments - Sudarnice Sudarnice (Integrated Journal of Business and Economics (IJBE), 2020)
This research was conducted to measure innovative performance of teachers at the State Vocational High School Kolaka, Kolaka District, Southeast Sulawesi Province. Variables used in this study are organizational culture, job satisfaction, organization commitment and innovative performance. Organization culture, job satisfaction as an independent variable in analyzing organization commitment variables. While other variables namely innovative performance as the dependent variable. Sampling technique in this study was to use a census method with a total of 98 respondents, while those collected were 82 questionnaires. Data analysis in this study uses smart PLS (Partial Least Square). Finding of this study found that organizational culture and job satisfaction have positive relationship on organization commitment. Moreover, organization culture, job satisfaction, and organizational commitment have positive relationship toward innovative performance.